Klustering Jumlah Penumpang pada Halte Bus Rapid Transit Kota Tangerang - Erni Dianawati; Putri Previa Yanti; Yulia Suryandari (Jurnal Sistem Cerdas, 2019)
Bus Rapid Transit (BRT) Trans Tangerang is a local public transportation system developed in the main corridor of the Tangerang City area as well as a feeder for Transjabodetabek and rail transport. BRT Trans Tangerang is one part of the Bus Rapid Transit program which is implemented and launched by Department of Transportation. The BRT Trans Tangerang system began operating at the beginning of December 2016. Some problems faced by Trans Tangerang Bus Rapid Transit such as the number of passengers that need to be increased to reduce congestion in the city of Tangerang and the placement of the right bus stops to attract passengers. Therefore, to overcome this problem, data and information about BRT Trans Tangerang are needed to find patterns of passenger distribution. The process of finding this information can be done by using data mining method. Within this method, there is a clustering technique which is useful to clustering all data in groups which have similar data. The algorithm used to classify the data is called simple k-means algorithm. In this study, all the data will be clustered into five cluster. The clustering results have almost the same nature between the data in one cluster, namely the total number of passengers per month, so that by performing clustering characteristics, knowledge of the busy schedule of passengers in one day can help related parties to anticipate the density of passengers on certain days.